2014
DOI: 10.1208/s12249-014-0243-3
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized Sustained Release Mucoadhesive Chitosan Sponges for Buccal Buspirone Hydrochloride Delivery: Formulation and In Vitro Evaluation

Abstract: Abstract. This work aims to prepare sustained release buccal mucoadhesive lyophilized chitosan sponges of buspirone hydrochloride (BH) to improve its systemic bioavailability. Chitosan sponges were prepared using simple casting/freeze-drying technique according to 3 2 factorial design where chitosan grade was set at three levels (low, medium, and high molecular weight), and concentration of chitosan solution at three levels (0.5, 1, and 2%). Mucoadhesion force, ex vivo mucoadhesion time, percent BH released af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…3a, the thermogram of Brz showed a glass transition temperature at 155°C and an exothermic peak at 221°C due to Brz oxidative degradation. The glass transition peak of Brz remained in PM but disappeared in Brz-LPs, which indicated that Brz was not in a crystalline state in the lipid matrix (17)(18)(19).…”
Section: Dsc Analysismentioning
confidence: 96%
“…3a, the thermogram of Brz showed a glass transition temperature at 155°C and an exothermic peak at 221°C due to Brz oxidative degradation. The glass transition peak of Brz remained in PM but disappeared in Brz-LPs, which indicated that Brz was not in a crystalline state in the lipid matrix (17)(18)(19).…”
Section: Dsc Analysismentioning
confidence: 96%
“…The comparison of the drying process on the PECs is thus not well reported. However, in the case of alginate (Ho et al, 2004;Quraishi et al, 2015) or chitosan (Kassem, ElMeshad, & Fares, 2014;Kim & Lee, 2011) pure films, the drying influence the structure of the resulting material. Hence, we think the drying process is a key point and propose a comparative study of simple processed PECs dried with either hot air, lyophilization or SCC drying.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, mucoadhesive delivery systems providing intimate contact between a dosage form and the vaginal mucosa have gained a great attention [3,4]. Among mucoadhesive polymers, chitosan (CS) is extensively studied in designing ocular [5], buccal [6], nasal [7], and vaginal dosage forms [8,9]. In addition, CS is currently receiving great interest in pharmaceutical and biomedical fields, particularly because of its penetration enhancement capability [10,11] and antifungal activity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%